La prescripción del ‘propietario’ y su impacto en la solución de los problemas vinculados a la determinación del derecho de propiedad - Pasco Arauco, Alan Augusto (2024)
The acquisitive prescription or usucapion turns out to be one of the most important figures in our regulations regarding property. As it turns out, it is not only a way to acquire the domain, but the only reliable way to prove ownership status. Along these lines, the present work makes a study of the concept of usucapion and its function as ‘proof of dominance’. This gives way to an analysis of the argument surrounding the ‘owner’s statute of limitations’, by examining national jurisprudence on the matter.Finally, to expose the practicality in the acceptance and application of the concept at a casuistic level. The author concludes that, through the acceptance of the theory of the ‘owner’s prescription’ and a correct application of it, it is possible to solve a series of controversies linked to the determination of the true owner.